Applying The 7P Marketing Mix Strategy In Promoting Islamic Education At Aqobah International School (AIS) Jombang - Imro’atus Solikah; Sulistyorini; Agus Eko Sujianto (International Journal of Education Management and Religion, 2026)
This study aims to analyze the implementation of the 7P marketing mix strategy in the context of educational service marketing at Aqobah International School (AIS) Jombang. The strategy encompasses seven key elements: product, price, place, promotion, people, physical evidence, and process. As a pesantren-based Islamic educational institution with an international vision, AIS has developed an integrative marketing approach to attract public attention, especially from parents seeking high-quality education embedded with strong religious values. Utilizing a descriptive qualitative approach, data were collected through participant observation, in-depth interviews, and document analysis. The findings indicate that implementing the 7P marketing mix strategy at AIS effectively strengthens the institution’s image and increases public interest in the educational programs offered.